Electrochemical studies of [Cu(phen)(c-mala)] N03, [Cu(phen)2CI2]·5.5H20, [Cu(phen)(edda)·5.5H20, and their interaction with DNA and H202 - Yaw, Chong Wey (2012)
Electrochemical characterization of the copper complexes; [Cu(phen)(c-mala)]NO3,[Cu(phen)2Cl2)5]·5.5H2O, and [Cu(phen)(edda)]·5H2O (phen= phenanthroline;c-mala = c-methylanaline; and edda = ethylenediaminediacetic) have been carried out using cyclic voltammetry (CV), chronocoulometry (CC), and chronoamperometry (CA). These copper(II) complexes were found to be electroactive as shown by its well defined redox waveforms during cyclic voltammetry. The results of double potential steps chronocoulometric (CC) studies show the presence of surface charge to be in the order of 10-4 C/cm2. A linear plot of log I versus log scan rate with slope of near 0.5 was obtained indicating the presence of a diffusion controlled process. The monotonic rising current transient observed during chronoamperometric studies provides another evidence of the diffusion controlled process. Based on hydrodynamic voltammetry studies, the diffusion coefficients of [Cu(phen)(c-mala)]NO3; [Cu(phen)2Cl2)5]·5.5H2O and [Cu(phen)(edda)]·5H2O were found to be of the order of 10-7 cm2/s. The interaction between copper(II) complexes and DNA and between copper(II) complexes and H2O2 were also investigated using cyclic voltammetry. The above electrochemical interaction was evident as their CV results revealing a slight shift in peak potential and a significant decrease in redox peak currents of Cu(II) complexes in the presence of DNA. It indicates that the interaction between the copper(II) complex with DNA molecule is via intercalation process. On the other hand, gel electrophoresis showed evident of deformation of DNA by the copper complexes. The “chemical nuclease” activity follows the order: [Cu(phen)2Cl2]•5.5H2O > [Cu(phen)(c-mala)]NO3 > [Cu(phen)edda]•5H2O > CuSO4.